2008
DOI: 10.1177/0731684408088888
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Partial Replacement of Paper Sludge by Commercial Fillers on Natural Rubber Composites

Abstract: The effects of partial or complete replacement of two commercial fillers, carbon black (CB) and silica on cure characteristics, tensile properties, fatigue life, morphological properties, and rubber-filler interaction of paper sludge (PS) filled natural rubber composites were elucidated. Compounding was carried out on a two-roll mill with total filler loading of 30 phr. Results indicate that maximum torque, tensile strength, elongation at break, tensile modulus, and fatigue life increased the cure time while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…The result shows that the scorch time and cure time of the composites decrease with increasing silica and the RHS loading in hybrid filler arrangement. This might be due to the matrix viscosity which is constantly increasing on addition of Silica and RHS [33,34] . This interactive filler dispersion helps in effective vulcanization and results in decreasing scorch time and cure time.…”
Section: Resultsmentioning
confidence: 99%
“…The result shows that the scorch time and cure time of the composites decrease with increasing silica and the RHS loading in hybrid filler arrangement. This might be due to the matrix viscosity which is constantly increasing on addition of Silica and RHS [33,34] . This interactive filler dispersion helps in effective vulcanization and results in decreasing scorch time and cure time.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of producing a composite with better mechanical performance is by the reinforcement by two or more types of filler in a single matrix leading to hybrid composites. The advantages of using a hybrid composite are, (i) synergistic effect of one filler to the other and (ii) the desired properties of each component could be combined [22]. The partial replacement of R-PET by commercial fillers has been reported previously [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the maximum weight loss of all composites was influenced by the commercial fillers. Chakraborty et al [22] reported that the amount of char or maximum weight loss is very much dependent on the type and amount of filler. The difference in filler amount mainly concerns char formation.…”
mentioning
confidence: 99%
“…Osman et al [11] studied the effect of maleic anhydride-grafted polypropylene (MAPP) on the properties of recycled newspaper (RNP) filled polypropylene (PP)/natural rubber (NR) composites and reported that the incorporation of MAPP reduced the water uptakes of the composites. The effects of partial or complete replacement of carbon black (CB) and silica on the properties of paper sludge (PS) filled natural rubber composites were elucidated by Ismail et al [12]. PS/silica filled natural rubber composites was reported to exhibit lower maximum torque, tensile properties and fatigue life compared to the PS/CB filled natural rubber composites.…”
Section: Introductionmentioning
confidence: 99%